KESAKSAMAAN PRINSIP-PRINSIP KESELAMATAN PRODUK SEBAGAI SEBAHAGIAN DARI ASPEK ‘ḤALĀLAN ṬAYYIBAN’ DENGAN PRINSIP-PRINSIP SYARIAH: The Similarity of Product Safety Principles as part of the ‘Ḥalālan Ṭayyiban’ Aspect with the Shariah Principles - Mohd Jalil, Nazatul Nabila; Zakaria, Zalina; Mohd Shoid, Nursyamimi Zawani (Jurnal Syariah, 2019)
Product safety is one of the main protections under the consumer protection regulations. It should be the primary aim in any consumer protection policy in every country, including Malaysia. This is due to the fact that there are a lot of consumer goods that are heterogeneous and more technologically advanced that are continually being introduced to consumers. The principle of product safety is in line with the principles laid down by Shariah. This article discusses the similarity of product safety principles as part of ‘ṭayyiban’ aspect with the Shariah principles.